New insights into the mechanism of action of the cyclopalladated complex - CP2 in Leishmania: Calcium Dysregulation, Mitochondrial Dysfunction and Cell Death - Velasquez, Angela Maria Arenas; Bartlett, Paula J.; Linares, Irwin A. P.; Passalacqua, Thais Gaban; Teodoro, Daphne D. L.; Imamura, Kely B.; Tosi, Luiz R. O.; Leite, Aline de L.; Buzalaf, Marilia A. R.; Velasques, Jecika M.; Netto, Adelino V. G.; Thomas, Andrew P.; et al. (American Society for Microbiology, 2021)
The current treatment of leishmaniasis is based on few drugs that present several drawbacks such as high toxicity, difficult administration route, and low efficacy. These disadvantages raise the necessity to develop novel antileishmanial compounds allied to a comprehensive understanding of their mechanisms of action. Here, we elucidate the probably mechanism of action of the antileishmanial binuclear cyclopalladated complex [Pd(dmba)(µ-N3)]2 (CP2) in Leishmania amazonensis. CP2 causes oxidative stress in the parasite resulting in disruption of mitochondrial Ca2+ homeostasis, cell cycle arrest at S-phase, increasing the ROS production and overexpression of stress-related and cell detoxification proteins, collapsing the Leishmania mitochondrial membrane potential and promotes apoptotic-like features in promastigotes leading to necrosis or directs programmed cell death (PCD)-committed cells toward necrotic-like destruction. Moreover, CP2 is able to reduce the parasite load in both liver and spleen in Leishmania infantum-infected hamsters when treated for 15 days with 1.5 mg/Kg/day CP2, expanding its potential application in addition to the already known effectiveness on cutaneous leishmaniasis for the treatment of visceral leishmaniasis, showing the broad spectrum of action of this cyclopalladated complex. The data herein presented bring new insights into the CP2 molecular mechanisms of action, assisting to promote its rational modification to improve both safety and efficacy.
Keywords: Binuclear cyclopalladated complex; cutaneous leishmaniasis; leishmanicidal activity; necrotic death in Leishmania; calcium homeostasis; mitochondria